THE DIDACTIC DIMENSION OF THE TEACHING- LEARNING PROCESS WITHIN THE LESSONS AIMED AT ORGANIZING ECONOMIC ACTIVITIES - Marius Costel ESI (Association of Social and Educational Innovation, 2020)
One of the important components considered in this research approach is given by the study on teaching-learning strategies, methods and techniques in the lessons aimed at organizing economic activities. It is understood that such a topic takes into account, on the one hand, a series of aspects related to an economic issue, and on the other hand, issues of a methodological / didactic nature found in the teaching-learning-assessment activity. At the same time, the approach that is intended to be highlighted reflects the practical-theoretical dimension of such a possible approach in class. Under these conditions, the research approach assumed involves an analysis focused, on the one hand, on the theoretical aspects related to the approached topic, and on the other hand, on the conceptual-theoretical operationalization with practical implications. In other words, thereis an interest in valorizing and capitalizing on the contents approached both theoretically and practically. Therefore, it is considered that we will analyze, from a theoretical and pragmatic perspective, the strategies, methods and teaching-learning techniques at the level of economic-themed classes, also revealing the impact it has in the economic-educational dimension.